If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (16x + 5y) * dx + (3x + y) * dy = 0 Reorder the terms for easier multiplication: dx(16x + 5y) + (3x + y) * dy = 0 (16x * dx + 5y * dx) + (3x + y) * dy = 0 Reorder the terms: (5dxy + 16dx2) + (3x + y) * dy = 0 (5dxy + 16dx2) + (3x + y) * dy = 0 Reorder the terms for easier multiplication: 5dxy + 16dx2 + dy(3x + y) = 0 5dxy + 16dx2 + (3x * dy + y * dy) = 0 5dxy + 16dx2 + (3dxy + dy2) = 0 Reorder the terms: 5dxy + 3dxy + 16dx2 + dy2 = 0 Combine like terms: 5dxy + 3dxy = 8dxy 8dxy + 16dx2 + dy2 = 0 Solving 8dxy + 16dx2 + dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'd'. d(8xy + 16x2 + y2) = 0 Factor a trinomial. d((4x + y)(4x + y)) = 0Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(4x + y)' equal to zero and attempt to solve: Simplifying 4x + y = 0 Solving 4x + y = 0 Move all terms containing d to the left, all other terms to the right. Add '-4x' to each side of the equation. 4x + -4x + y = 0 + -4x Combine like terms: 4x + -4x = 0 0 + y = 0 + -4x y = 0 + -4x Remove the zero: y = -4x Add '-1y' to each side of the equation. y + -1y = -4x + -1y Combine like terms: y + -1y = 0 0 = -4x + -1y Simplifying 0 = -4x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 3
Set the factor '(4x + y)' equal to zero and attempt to solve: Simplifying 4x + y = 0 Solving 4x + y = 0 Move all terms containing d to the left, all other terms to the right. Add '-4x' to each side of the equation. 4x + -4x + y = 0 + -4x Combine like terms: 4x + -4x = 0 0 + y = 0 + -4x y = 0 + -4x Remove the zero: y = -4x Add '-1y' to each side of the equation. y + -1y = -4x + -1y Combine like terms: y + -1y = 0 0 = -4x + -1y Simplifying 0 = -4x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| x*x=-36 | | 2x^3-8x^2-14x= | | 10x=4.09 | | n^3-n-3360=0 | | e^1-7x=9 | | (6-v)(3v-4)=0 | | x=2600 | | x-.2=13000 | | x*x=5 | | 4x+1=25-2x | | 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 | | o^2+0o+-4=0 | | -7=p-5 | | 6s^2+3s=0 | | 802.1-4.82+9= | | y-9=-19 | | 4r^2+30r+10=0 | | 24=4n | | 8(x+12)-288=3x | | 3q+4=2q+10 | | 2x^2+8x=192 | | 8x+35=6x+27 | | n^2+-3n+-40=0 | | 7x+1=52 | | 10v^2-21v-49=0 | | 2x^3+8x^2-64=0 |